Pendampingan Peningkatan Kapasitas Sdm Pariwisata Di Kawasan Borobudur Kabupaten Magelang - Pranoto Pranoto; Haniek Listyorini; Gana Wuntu (CV. ALIM'SPUBLISHING, 2026)
The Borobudur area, Magelang Regency, has experienced a significant decline in tourist visits following the implementation of stricter management regulations for Borobudur Temple, including daily visitor quotas, session-based visiting systems, mandatory upanat sandal usage (since December 2023), and perceptions of high ticket prices. Tourist visits declined by more than 50 percent during the 2025 Eid holiday period compared to the previous year, impacting the entire tourism supply chain in the area. One of the identified root causes is the unpreparedness of local tourism human resources (HR) in adapting to regulatory changes and service standards. This community service activity was conducted by the STIEPARI Semarang lecturers' team through structured mentoring of 100 tourism practitioners from seven HR groups: tour guides, homestay managers, tourism transportation managers, souvenir centre managers, food and beverage managers, tourism destination managers, and Balkondes managers. The activity ran over three months (March–May 2026) using interactive lectures, workshops, demonstrations, FGDs, field simulations, and role plays, with pre- and post-test evaluations. Results showed an average competency improvement of 29.7 percent (from 49.2% to 78.9%), with the highest improvement among Balkondes managers (34.4%) and souvenir centre managers (32.6%). In addition to individual competency gains, the activity produced an institutional outcome: the establishment of the Borobudur Cross-Sector Tourism Community Forum as a coordination platform for sustainable tourism ecosystem development in the Borobudur area.